Students´ perception of interprofessional education in the bachelor programme “Interprofessional Health Care” in Heidelberg, Germany: an exploratory case study - Mahler, Cornelia; Schwarzbeck, Veronika; Mink, Johanna; Götz, Katja (BMC medical education, 2018)
Interprofessional education is receiving increased attention worldwide. This has led to the development of a bachelor programme “Interprofessional Health Care” at the University of Heidelberg, Germany beginning in the winter semester 2011. Aim of this study was to evaluate the students’ perception of this innovative programme regarding interprofessional learning.